Visual Communication in the Design of the "Fathiyah" Application as a Learning Media for Hijaiyah Letters in the COVID-19 Period - Vernanda Em Afdhal; Wulandari Wulandari; Widia Marta (Jurnal Teknologi Informasi dan Pendidikan, 2021)
The development of scientific technology is increasingly experiencing very rapid changes, especially in gadget technology. Learning media has undergone many transformations and has become a tool in the success of the teaching and learning process. Meanwhile interactive multimedia is a media that combines audio, video, illustration, animation and text that is packaged interactively and integrated. Hijaiyah letters are letters found in the Koran and become a script system in the Arabic alphabet or alphabet. Referring to the needs in the world of education, media development is significantly relevant to the era of the digital world. Moreover, the lack of face-to-face contact in the era of the COVID-19 pandemic is one of the reasons for the reduced interaction in education. The existence of the "Fathiyah" application can be an alternative learning media in learning and understanding hijaiyah letters during the pandemic. The purpose of this research is to design visual communication media in the form of applications to be problem solving for learning media about hijaiyah letters during the covid-19 pandemic. The method in application design adapts the waterfall method which departs from the design construction process starting from needs analysis to the maintenance stage. The results of the maintenance of the waterfall method can be updated regularly in accordance with the development of learning methods. For data analysis, the SWOT analysis method will be used. From the design of this learning media, it produces an application in which there is a form of visual communication that is used as a learning tool and as a strategy in promoting the "fathiyah" application brand. In addition to Android-based applications, visual communication is also applied as a form of brand building process or supporting media such as express books, folding tables, web banners, x-banners, motion graphics, t-shirts, posters, stickers, keychan and CDs.